2013
DOI: 10.1371/journal.pone.0071228
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DO as the Optimizer of Epitope Selection for MHC Class II Antigen Presentation

Abstract: Processing of antigens for presentation to helper T cells by MHC class II involves HLA-DM (DM) and HLA-DO (DO) accessory molecules. A mechanistic understanding of DO in this process has been missing. The leading model on its function proposes that DO inhibits the effects of DM. To directly study DO functions, we designed a recombinant soluble DO and expressed it in insect cells. The kinetics of binding and dissociation of several peptides to HLA-DR1 (DR1) molecules in the presence of DM and DO were measured. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 69 publications
2
30
1
Order By: Relevance
“…Poluektov et al . [137] reported a similar effect, and recently acidic pre-treatment of DM or DM–DO was shown to modulate peptide-exchange activity of DM [138]. However, to date, it is assumed that DO affects antigen presentation of peptides that are bound to MHCII proteins under mildly acidic conditions [135].…”
Section: The Central Role Of Hla-dm In Mhcii Antigen Presentationmentioning
confidence: 94%
“…Poluektov et al . [137] reported a similar effect, and recently acidic pre-treatment of DM or DM–DO was shown to modulate peptide-exchange activity of DM [138]. However, to date, it is assumed that DO affects antigen presentation of peptides that are bound to MHCII proteins under mildly acidic conditions [135].…”
Section: The Central Role Of Hla-dm In Mhcii Antigen Presentationmentioning
confidence: 94%
“…Similarly, DO expression is generally required for high expression of class II invariant chain peptides (CLIP) presentation at the cell surface; new work from the Pezeshki et al shows that this increases binding of particular superantigens, SEA and TSST-1 [45]. The finding that HLA-DO is a competitive inhibitor of DM action would appear to indicate that DO acts simply by attenuating DM, and not, for example, by modulating DM specificity [3], although Poluektov et al have proposed an additional role for HLA-DO in direct interaction with MHC-II [46]. …”
Section: Progress In Elucidating the Elusive Role Of Do In Immunitymentioning
confidence: 99%
“…Another attempt toward understanding the role of DO in peptide selection was recently published (43). In this study authors found differences in how DO affected loading of different peptides onto DR1.…”
Section: Mechanisms Of Hla-do Functionmentioning
confidence: 99%